Adsorption of Antibiotics in Wastewater by Stevia rebaudiana Zinc Oxide Nanoparticles - Guirguis, Hania (AUC Knowledge Fountain, 2023)
Green zinc oxide nanoparticles (ZnO NPs), synthesized using Stevia rebaudiana extract, are investigated as novel adsorbents for the removal of the antibiotics ciprofloxacin (CIP) and tetracycline (TET) from water. The green ZnO NPs were synthesized using a novel, rapid and ecofriendly technique that utilized a natural source with high sugar content as a reducing agent and a less energy intensive approach that did not require annealing or calcination at high temperatures. The particles are mesoporous, with a hexagonal wurtzite structure, a BET surface area of 15.28 m2/g and a size range of 37.36-71.33 nm. At pH 5, the green ZnO NPs have a negative surface charge of -15 mV, indicating their colloidal stability. The synthesis process was evaluated by a stepwise regression statistical model to examine the effect of synthesis parameters on particle size. Additionally, the green ZnO NPs were found to exhibit an antioxidant activity of 85.57% at 250 μg/mL and antibacterial activity against both E. coli and S. aureus. As for adsorption, the best results for CIP were achieved at 125 mg/L initial concentration, 4g/L dose, pH 5 and 25 °C after 60 min, yielding 86.77±0.82% removal and 27.07±0.26 mg/g adsorption capacity. For TET, the highest adsorption capacity of 15.88±0.37 mg/g was obtained at 125 mg/L while the highest % removal of 67.86±3.41%, was achieved at 25 mg/L using 4g/L dose, at pH 5 and 25 °C after 120 min. The adsorption process was evaluated by a stepwise regression statistical model for optimization of the operating parameters. The adsorption of CIP and TET by the green ZnO NPs was best described by the Langmuir isotherm and pseudo-second order kinetics. Various binding adsorption mechanisms were suggested, including van der Waals forces, hydrogen bonding and electrostatic interactions. The regeneration and reuse of the adsorbent was possible for 5 cycles. In effect, the green ZnO NPs could be efficiently utilized as a simple, rapid, reusable and low-cost adsorbent for the removal of CIP and TET from wastewater and could be further applied on other emerging contaminants.